1992
DOI: 10.2135/cropsci1992.0011183x003200020032x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Partitioning in Maize during Ear Development

Abstract: The partitioning of N during the grain‐filling period of maize (Zea mays L.) was studied under field conditions at differing levels of fertilizer. Two hybrids with differing leaf‐canopy senescence, B73Ht × LHI05 (rapid) and B73Ht × Va35 (slow), were grown with two rates (67 and 257 kg ha−1). Separate plants were supplied with 15N the 14‐leaf stage (VI4), antbesis, or 22 d after anthesis, and the subsequent patterns of 15N partitioning were followed. Independent of time of application, hybrid, or N fertility, ⊄… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
99
0
15

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(123 citation statements)
references
References 0 publications
9
99
0
15
Order By: Relevance
“…There are two sources of N for grain growth: concurrently absorbed N from the soil during post-silking and remobilization from pre-silking accumulated N of vegetative tissues (Ta and Weiland, 1992;Chen et al, 2014c). In the present study, N accumulation amounts during post-silking stage and pre-silking N uptake by SP treatment were both significantly decreased.…”
Section: Discussionmentioning
confidence: 99%
“…There are two sources of N for grain growth: concurrently absorbed N from the soil during post-silking and remobilization from pre-silking accumulated N of vegetative tissues (Ta and Weiland, 1992;Chen et al, 2014c). In the present study, N accumulation amounts during post-silking stage and pre-silking N uptake by SP treatment were both significantly decreased.…”
Section: Discussionmentioning
confidence: 99%
“…This element is closely linked to the production of important constituent proteins for embryo initial development during seeds germination, with great effects on grain yield. For grain filling, two sources of nitrogen are used, one originated from soil absorption and the other from remobilization of vegetative tissues (Ta & Weiland, 1992).…”
Section: Nitrogen (N)mentioning
confidence: 99%
“…In case of abiotic stresses due to drought or nitrogen deficiency, there is a possibility of remobilizing this element from vegetative tissues to the grains (Ta & Weiland, 1992;Carvalho et al, 2013). Research by Carvalho and Nakagawa (2012) defines that nitrogen influence seeds physiological quality, however their effects depend on environmental conditions and plant development stage.…”
Section: Nitrogen (N)mentioning
confidence: 99%
“…The N required for developing ears and grain-filling was predominantly contributed by root absorption from soil at vegetative stages. Ta and Weiland (1992) reported that during anthesis and grain filling stages, even though roots continued to take up N from the soil, up to 90% of N required for the ear development Can. J.…”
Section: Grain Yield and Stover Dry Mattermentioning
confidence: 99%